A Novel Closed-Chest Porcine Model of Chronic Ischemic Heart Failure Suitable for Experimental Research in Cardiovascular Disease. (15th September 2013) - Biondi-Zoccai, Giuseppe; De Falco, Elena; Peruzzi, Mariangela; Cavarretta, Elena; Mancone, Massimo; Leoni, Omar; Caristo, Maria Emiliana; Lotrionte, Marzia; Marullo, Antonino G. M.; Amodeo, Antonio; Pacini, Luca; Calogero, Antonella; et al.
Abstract : Cardiac pathologies are among the leading causes of mortality and morbidity in industrialized countries, with myocardial infarction (MI) representing one of the major conditions leading to heart failure (HF). Hitherto, the development of consistent, stable, and reproducible models of closed-chest MI in large animals, meeting the clinical realism of a patient with HF subsequent to chronic ischemic necrosis, has not been successful. We hereby report the design and ensuing application of a novel porcine experimental model of closed-chest chronic ischemia suitable for biomedical research, mimicking post-MI HF. We also emphasize the key procedural steps involved in replicating this unprecedented model, from femoral artery and vein catheterization to MI induction by permanent occlusion of the left anterior descending coronary artery through superselective deployment of platinum-nylon coils, as well as endomyocardial biopsy sampling for histologic analysis and cell harvesting. Our model could indeed represent a valuable contribution and tool for translational research, providing precious insights to understand and overcome the many hurdles concerning, and currently quenching, the preclinical steps mandatory for the clinical translation of new cardiovascular technologies for personalized HF treatments.